Effect of mobile messenger strategy on achievement among sixth grade students in geography - سعید, هەردی سعید فرج أمین; علی, ا.م.د احمد علی حمه‌; قادر, ا.م.د بشری قادر كريم زەنگەنە (Sulaimani Journal for Humanities, 2025)
This study discusses the effect of mobile messenger strategy on achievement among sixth grade students in geography. The aim of this study is to know (the effect of using mobile messenger strategy on achievement among sixth grade students in geography). The research community consists of sixth grade students in the center of Halabja province. To determine the sample of the research, the researcher chose (Bana Primary School). Two groups were randomly selected for the sample, which numbered (38) students (c) was the experimental group with 19 students and branch (a) was the control group with 19 students. Then the researcher balanced the variables between the two groups (previous year's geography score, age, intelligence level, parents' education During the experiment, he selected three chapters from the book of social subjects, in order to formulate the research objectives and according to the nature of the content of the subject (95) formulated objectives based on Bloom's classification of cognitive levels It consisted of (30) test items of the type (choice) according to the creation of the test map, to ensure the accuracy of the test items, was made available to a group of experts, to stabilize the researcher re-tested the test method Then using T.test to statistic the data, the researcher relied on spss 26 for statistical analysis. The results show that there is a statistically significant difference between the mean scores of the experimental group and the control group In the light of the results, the researcher reached several conclusions that generally emphasize the effectiveness of the mobile messenger strategy in teaching, and finally the researcher proposed several titles for researchers to research in the future
Keywords: impact; strategy; instant messaging applications; achievement